Transmission of the traumatic past: postmemory and teaching of recent history (Clío & Asociados. La historia enseñada. ISSN: 2362-3063, 2018)
The study of post memory focuses on the ways of remembering second generations to which traumatic pasts have been transmitted to them, as well as on the ways in which this transmission takes place. According to Marianne Hirsch (2012), post memory is configured when the memories of the generation that precedes a subject take the strength to consider them as their own experiences. In this way, studying postmemory requires analyzing the ways in which second generations interrogate their past to define their own space as political subjects. Within the field of recent history in Argentina, in recent years there has been growth in studies that analyze artistic works of the second generation around the parameters of postmemory. Beyond the diversity of investigations that address such works in depth, the objective of this analysis is to observe what questions can contribute to answer the post-memory and what perspectives can help to reconstruct in relation to the teaching of recent history.
Keywords: recent history; teaching; post memory; second generation